Foreign language MOOCs design: challenges to provide meaningful learning - Rocha, Cláudia Hilsdorf (The ESPecialist, 2018)
This paper aims at presenting theoretical discussions and guidelines to support the development of a MOOC (Massive Online Learning Courses) related to academic literacies in the teaching and learning of Brazilian Portuguese as a foreign language. Firstly, some reflections about Language MOOCs as an emergent field are presented. After that, some discussions concerning the conceptualization of Language MOOCs design are carried out, followed by considerations regarding appropriate pedagogies for this kind of courses. Finally, the main challenges for the development of LMOOCs nowadays are approached.